Resistance to Marriage, Family Responsibilities, and Mobility: A Turbulent Life Story from Kyidrong (HIMALAYA, 2023)
Tsering, the eldest of three daughters in a sonless household, was designated to perpetuate the family by marrying a matrilocally resident husband. She did not like the chosen man and thus decided, against her family’s wishes, to remain single. Tsering was subsequently caught up in the destruction of Tibet’s religious institutions and social order during the Cultural Revolution. As border dwellers, her family escaped to Nepal when persecution became too intense, but then returned once the situation stabilized. Because Tsering’s mother decided to remain in Nepal, she accepted her duty of caring for an aging parent and never returned to her natal village. Tsering’s life story sheds light on the nexus of gender, social status, and mobility among Tibetan commoners during the turbulent mid-twentieth century. It underscores how women in Kyidrong had agency, albeit the consequences of resisting marital expectations could be substantial even in a society where female non-marriage was both common and acceptable.Note: To have Tibetan script correctly displayed, please download the PDF file and open it in a desktop application.